The Transcriptome of Exophiala dermatitidis during Ex-vivo Skin Model Infection - Poyntner, Caroline; Blasi, Barbara; Arcalis, Elsa; Mirastschijski, Ursula; Sterflinger, Katja; Tafer, Hakim (Frontiers in Cellular and Infection Microbiology, 2016)
The black yeast Exophiala dermatitidis is a widespread polyextremophile and human pathogen, that is found in extreme natural habitats and man-made environments such as dishwashers. It can cause various diseases ranging from phaehyphomycosis and systemic infections, with fatality rates reaching 40%. While the number of cases in immunocompromised patients are increasing, knowledge of the infections, virulence factors and host response is still scarce. In this study, for the first time, an artificial infection of an ex-vivo skin model with Exophiala dermatitidis was monitored microscopically and transcriptomically. Results show that Exophiala dermatitidis is able to actively grow and penetrate the skin. The analysis of the genomic and RNA-sequencing data delivers a rich and complex transcriptome where circular RNAs, fusion transcripts, long non-coding RNAs and antisense transcripts are found. Changes in transcription strongly affect pathways related to nutrients acquisition, energy metabolism, cell wall, morphological switch, and known virulence factors. The L-Tyrosine melanin pathway is specifically upregulated during infection. Moreover the production of secondary metabolites, especially alkaloids, is icreased. Our study is the first that gives an insight into the complexity of the transcriptome of Exophiala dermatitidis during artificial skin infections and reveals new virulence factors.